2009
DOI: 10.1007/s11250-009-9436-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathotyping of a Newcastle disease virus isolated from peacock (Pavo cristatus)

Abstract: This report describes Newcastle disease in peacock and the isolation and characterization of the virus. The virus had an intracerbral pathogenicity index of 1.71 and mean death time of 47 h. The isolate had multiple basic amino acids at the fusion protein cleavage site sequence ((110)GGRRQRRFIG(119)) with a phenylalanine at residue 117. Biological and molecular characterization revealed that the virus is velogenic. Phylogenetic analysis placed the isolate in genotype II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 12 publications
0
18
3
Order By: Relevance
“…Mortality in peacock was observed with congestion of lungs and intestinal mucosa. NDV outbreaks in peafowls have been reported earlier from India and other part of the world [14,28]. Contrary to our findings Vijayarani et al [28] reported the absence of characteristics NDV signs in birds.…”
contrasting
confidence: 96%
See 1 more Smart Citation
“…Mortality in peacock was observed with congestion of lungs and intestinal mucosa. NDV outbreaks in peafowls have been reported earlier from India and other part of the world [14,28]. Contrary to our findings Vijayarani et al [28] reported the absence of characteristics NDV signs in birds.…”
contrasting
confidence: 96%
“…NDV outbreaks in peafowls have been reported earlier from India and other part of the world [14,28]. Contrary to our findings Vijayarani et al [28] reported the absence of characteristics NDV signs in birds. Postmortem lesions that included congestion in lungs and intestinal mucosa were similar to those observed previously by Vijayarani et al [28] and were also indicative of NDV infection.…”
contrasting
confidence: 96%
“…There is only one report with respect to the genotyping of a NDV isolate from peacock in India employing the well characterized molecular determinant the FPCS [42]. This report points to the prevalence and circulation of genotype II virus in India.…”
mentioning
confidence: 95%
“…Most of the reports had not only looked into the biological characteristics of the virus but also sequenced the FPCS to determine the virulence of the virus [21,22,24,42]. There are also reports on isolation, biological characterization and FPCS sequence based pathotyping of NDV from backyard chicken [6] and other species of birds such as pigeons [18,24,40,42,46] Japanese quail [21], Turkey [37], Duck [47], crow [31], Emu [23] and Ostrich [45].…”
mentioning
confidence: 99%
See 1 more Smart Citation